Drag reduction in microfluidic - Ling Wang Ming, Fiona (2015)
Frictional force is an unavoidable problem in transportation in pipeline which will cause a great pressure drop in the pipeline. Currently, industries use pumps to maintain the pressure in the pipeline for transportation. In order to solve this problem, researchers were developing drag reduction technique using different types of materials to get an alternative for pumps. Drag reduction is a technique where a minute of amountof drag reduction additives, usually parts per million (ppm), is added into liquid which reduce the frictional drag greatly. However, researches are mostly done in macroscale where there will be a waste in reagent. In this experimental study, investigation the effect of variable concentration of nanopowders with different size of microchannels and different flow rate on drag reduction is carried out. The nanopowder (Bismuth (III) oxide, Iron (II,III) oxide, Silica and Titanium (IV) oxide) is dissolved in DI water and the fluid is pumped into microchannels with the width and depth of 50μm, 100μm and 200μm respectively which is connected to pressure transmitter through syringe pump. Nanopowder is an effective drag reduction additive with the drag reduction up to more than 64%. It is believed that Iron (II, III) oxide is the most effective DRA